Risk assessment, occupational safety implementation and practices with an intervention of safety signs and lines for primary school pupils in LMS district, Perak - Subramaniam, Murugan (2020)
The objective of this study were to assess the risk of school safety, evaluate occupational safety implementation and practices in schools and to intervene newly modified safety signage and safety lines for the intervention and control group among the primary school pupils in Larut, Matang and Selama district, Perak state, Malaysia. This study was carried out into three phases. The first phase is risk assessment with the aim to identify hazards and calculate risk rating (RR). The second phase is to evaluate occupational safety practices and implementation in primary schools. The third phase which is to intervene newly modified safety signs and lines by testing selected primary school pupils knowledge. 110 schools in LMS district was assessed using risk assessment form. Risk Matrix Table was used to categorize the schools either in low, moderate or high risk based on hazards. For the second phase, 102 (91.9%) schools safety coordinator’s were questioned about the implementation of occupational safety and practices in their school. In the third phase of study, newly modified safety signages were designed by modifying current safety signage according to MS2558:2014 standard. All the signages was modified with drawn pictures and texts according to identified hazards from the risk assessment. Cluster sampling and randomization procedures was used in selection of school for intervention. The intervention of newly modified safety siganges and lines was done in a school which scored highest RR value from 110 schools (intervention group). Pre-test, post-test and post-test 2 (after 3 months for intervention school only) was done among 303 pupils from intervention group and compared with 465 pupils from control group to test their knowledge on newly modified safety signages and lines. All the data was analyzed using SPSS version 25. The analysis shows that only one school was in high risk (RR 16), 93.6% of schools in medium risk (RR5 - RR9) and 5.5% in low risk (RR4). 82.7% schools have improper grates for drains (RR 12), 93.6% of schools did not fence their septic tank area (RR 12) and all the schools have uneven corridor floor with patches, trip and slope (RR 16). Safety coordinators knowledge on occupational safety legislation (75.5%) were poor. Safety programmes only focused on fire safety drill. Intervention for all the newly modified safety signs and lines showed significant different between pre-test, post-test and post-test 2 for intervention group (p < 0.001) and pupils were able to sustain the meaning of safety signage and lines after three months’ time. For the control group, 15 out of 25 safety signages and lines, shows not significant different with p > 0.05 between pre-test and post-test. Mean rank different on safety signages and safety lines knowledge scores between intervention and control group was significant (p<0.05). Majority of the schools in LMS district are in medium risk. Implementation and practices of occupational safety in all the primary schools are still lacking and have to be improved. The newly modified safety signages and lines able to promote safety knowledge and can prevent injuries effectively in future.